The effect of cholestyramıne on dogs with acute digoxin toxicosis - Abdullah Başoğlu; Mehmet Maden; Kemal Çiftçi; İdris Akkuş; Abdurrahim Koçyiğit; Fatih Hatipoğlu; Hüseyin Akbulut (Eurasian Journal of Veterinary Sciences)
in this study, the effects of cholestyramine on the clinical, laboratory and histopathologic findings in dogs with acute digoxin toxicosis was induced by intravenouse injection of digoxin at the dose of 0.1 mg/kg in two groups of dogs (control and experimental groups) and elinical pathologic, histopathologic and e!ectrocardiographic findigs and changes in serum digoxin concentrations were eva!uated. lncriments in red b!ood eel! count (RBC), blood urea nitragen (BUN) and serum uric acide. Potassium and digoxin concentrations and decreaments in serum sodium and chlorid concentrations were found to be significant in control group of dogs while changes in this paramaters were not found to be significant in experimental group of dogs treated with cholestyramine. At the histopathologic examinataions of both groups of dogs, the pathologic lesions in coroner arteries, myocardium and kidneys in control group of dogs were more severe than that of experimental group of dogs anda dog in control group died during the experiment. The result of the study showed that acute digoxin toxicosis caused significant changes elinical pathologic and histopathologic significant changes, elinical pathologic and histopathologic findings and the treatment of acute digoxin toxicosis with cholestyramine would be benefical in dogs.